2002
DOI: 10.1034/j.1399-6576.2002.460707.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidural blood patch for management of postdural puncture headache in adolescents

Abstract: Epidural blood patch seems to be an effective and safe procedure in adolescents for treating severe and persistent PDPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 24 publications
3
43
0
1
Order By: Relevance
“…It is possible that these patients did not get enough information concerning treatment of headache or fear of the procedure kept them home. While drugs in treatment of PDPH are usually ineffective [19], epidural blood patching is safe, fast and effective in 90% of patients; and if repeated in patients showing a poor response the response rate rises up to 98% [20][21][22][23]. Despite that, epidural blood patch is underused in the treatment of patients with diagnostic lumbar puncture.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these patients did not get enough information concerning treatment of headache or fear of the procedure kept them home. While drugs in treatment of PDPH are usually ineffective [19], epidural blood patching is safe, fast and effective in 90% of patients; and if repeated in patients showing a poor response the response rate rises up to 98% [20][21][22][23]. Despite that, epidural blood patch is underused in the treatment of patients with diagnostic lumbar puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 40 articles to which we refer and which were published between 1990 and 2002, 9 review existing literature and refer to numerous studies but often do not mention how many patients are included in the studies [5,7,8,10,11,13,15,23,34]. Twenty-one articles are prospective studies, referring to other studies in the discussion [3,6,9,12,14,16,17,18,19,20,21,22,25,28,32,33,35,37,38,39,41]; four are retrospective studies [1,26,31,40], three are case reports followed by literature review [4,27,36]; two editorials [2,29] and one is a letter [30].…”
Section: Introductionmentioning
confidence: 97%
“…Clinical experience has shown that epidural blood patch by preventing leakage through occluding the perforation is an effective therapy to treat a persistent post-spinal headache, with a success rate of more than 90% (3,4,5,34). However, as mentioned in the Introduction, a small CSF leakage is not compatible with a marked symptomatic influence on pain-sensitive regions of the brain, and especially not with the postural properties of the post-spinal headache, or the fact that the headache often disappears promptly after application of the blood patch.…”
Section: Discussionmentioning
confidence: 99%
“…The headache may be intolerable (1)(2)(3)(4) and can continue for days and even for weeks. In most cases it is of temporary nature, but specific treatment such as application of epidural blood patch is sometimes necessary for its disappearance (4,5). The mechanisms behind post-spinal headache are still unknown.…”
Section: Introductionmentioning
confidence: 99%